2022
DOI: 10.3390/applmech3010011
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review of Selected Biomechanical Variables for Sport Performance Monitoring and Training Optimization

Abstract: Traditional neuromuscular tests (e.g., jumping and sprinting tasks) are useful to assess athletic performance, but the basic outcomes (e.g., jump height, sprint time) offer only a limited amount of information, warranting a more detailed approach to performance testing. With a more analytical approach and biomechanical testing, neuromuscular function can be assessed in-depth. In this article, we review the utility of selected biomechanical variables (eccentric utilization ratio, force–velocity relationship, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 93 publications
0
6
0
2
Order By: Relevance
“…Seeking to expand upon this compelling aspect, several scholars have in fact confirmed that there is a close relationship between the capacity of producing high forces and superior swimming performances. To this scope, a reliable tool used to assess swimming-specific strength (both on dry land as well as in the water) is the evaluation of force–velocity exertion, which basically dictates the relationship between the load lifted and the speed it can be moved [ 16 , 17 ]. Specifically, it has been shown that high levels of maximum strength in various exercises (e.g., bench press, pull-up, back squat, horizontal rows, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Seeking to expand upon this compelling aspect, several scholars have in fact confirmed that there is a close relationship between the capacity of producing high forces and superior swimming performances. To this scope, a reliable tool used to assess swimming-specific strength (both on dry land as well as in the water) is the evaluation of force–velocity exertion, which basically dictates the relationship between the load lifted and the speed it can be moved [ 16 , 17 ]. Specifically, it has been shown that high levels of maximum strength in various exercises (e.g., bench press, pull-up, back squat, horizontal rows, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The results of biomechanical evaluations are crucial for assessing athletic performance because they offer a more thorough understanding of a person's neuromuscular capabilities, which traditional testing may miss (Pleša et al, 2022). Understanding the mechanics of any sport is essential for improving performance and avoiding injuries, and biomechanics can help with this (Kumaran et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the aforementioned methods of assessing JH rely upon a single point on the body to reflect JH rather than a more functional and realistic tracking of the total body center of mass (TBCM). Furthermore, while JH may directly reflect performance ability in sports that involve jumping ( Souza et al, 2020 ), assessing the underlying neuromuscular components contributing to the CMJ via force plate technology provides an enhanced perspective of monitoring training adaptations ( Claudino et al, 2017 ; Gathercole et al, 2015a ; Pleša et al, 2022 ), fatigue ( Cormack et al, 2008 ; Gathercole et al, 2015a ), and recovery from musculoskeletal injury ( Baumgart et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%